Enhancing Collaborative Manipulation Through the Use of Feedback and Awareness in CVEs - Garcia, Arturo S.; Molina, José P.; Martínez, Diego; González, Pascual (International Journal of Virtual Reality, 2009)
In the research community, Collaborative Virtual Environments (CVEs) developers usually refer to the terms awareness and feedback as something necessary to maintain a fluent collaboration when highly interactive task have to be performed. However, it is remarkable that few studies address the effect that including special kind of awareness has on the task performance and the user experience.This paper proposes how to face the implementation of awareness in order to be taken into account early in the development of a CVE. In addition, it is also described an experiment that was carried out to evaluate the effect of providing some visual cues, showing that users tend to make more mistakes when they are not provided.